Occupancy-equivalent, operative temperature control for an energy-saving operation of direct electric, low-capacity heating systems. (December 2022) - Schmitt, Lukas; Schaub, Michael; Brandt, Stefan; Kriegel, Martin
Abstract: Conventional heat supply systems for indoor environments merely show annual efficiencies of net energy usage for room heating of 70 % to 80 % due to an inertia-related oversupply in unoccupied periods. In this study, a new method for increasing this efficiency is introduced. Low-capacity, direct electric heating systems are used to realize an occupancy-equivalent heating concept which only heats the room during occupancy. Using a fast-responding infrared sensor, these heating systems can be controlled by operative temperature, preventing significant oversupplies whilst rapidly heating up a space. A model-based algorithm enables a setback of the room temperature in unoccupied periods while guaranteeing a predefined temperature in the beginning of occupied periods. Thus, the control algorithm enables a utility-equivalent heating operation compared to a non-setback operation. During a first parameter study, net energy savings of up to 21 % could be realized due to the new control method compared to a conventional schedule-based operation. The reheating factor of the heat supply system is identified as the main indicator affecting the energy saving potential in occasionally occupied rooms. Highlights: Infrared sensor is suitable for control of low-capacity, radiative heating systems. Low-capacity heating systems allow energy-efficient, intermittent heating. Thermal comfort is utility-equivalent to a non-setback operation. Higher reheating factor enlarges energy savings.